KESESUAIAN PEMANFAATAN RUANG UNTUK MENJAGA DAN MENGONTROL KEBERLANGSUNGAN FUNGSI KAWASAN RESAPAN AIR TERHADAP PERKEMBANGAN WILAYAH DI KECAMATAN KWANDANG - Juni Akbar, La Ode; Antule III, Andri Darmawan; Cono , Titi Hawanda Metania (Universitas Bina Taruna Gorontalo, 2024)
The research aims to control and preserve the function of water catchment areas so that the ecological benefits are maintained, and support environmental sustainability for sustainable development. The research method that can be used in this study is descriptive analytical method. Compiling a description of the existing RTRW and the actual condition of the water catchment area and analyzing the suitability between the two, whether the planned use of space is in accordance with existing conditions or has the potential to damage water catchment. Using Geographic Information System (GIS) to map and compare the location of water catchment areas with the land use map listed in the RTRW. The land cover class based on the results of the analysis shows that the Somewhat Large infiltration class group has the largest area, namely 16,932.80 ha. The Small infiltration class has an area of 2648.55 ha and the Medium infiltration class has the smallest area of 26.67 ha. Based on the type of land use, the limited production forest area has an area of 11,196 ha and is the largest type of land use in the kwandang sub-district, while the land use area for the Active Fault Line has the smallest area of 26.67 ha. Condition of water catchment area based on natural and actual infiltration overlay. Good condition (cB, dB) covers 78.16% of the total area, Normal Natural condition (bB, cC) covers 8.23%, Starting Critical condition (bC, dE) covers 0.1%, Somewhat Critical condition (cE) covers 10.57%, which indicates areas that have experienced a significant decrease in water infiltration capability. Critical condition (bE) covers 2.92%.